Otitis media susceptibility and shifts in the head and neck microbiome due to variants. - Frank, Daniel N; Giese, Arnaud P J; Hafrén, Lena; Bootpetch, Tori C; Yarza, Talitha Karisse L; Steritz, Matthew J; Pedro, Melquiadesa; Labra, Patrick John; Daly, Kathleen A; Tantoco, Ma Leah C; Szeremeta, Wasyl; Reyes-Quintos, Maria Rina T; et al. (J Med Genet, 2020)
BACKGROUND: Otitis media (OM) susceptibility has significant heritability; however, the role of rare variants in OM is mostly unknown. Our goal is to identify novel rare variants that confer OM susceptibility. METHODS: We performed exome and Sanger sequencing of >1000 DNA samples from 551 multiethnic families with OM and unrelated individuals, RNA-sequencing and microbiome sequencing and analyses of swabs from the outer ear, middle ear, nasopharynx and oral cavity. We also examined protein localisation and gene expression in infected and healthy middle ear tissues. RESULTS: A large, intermarried pedigree that includes 81 OM-affected and 53 unaffected individuals cosegregates two known rare variants, a common variant and a rare, novel pathogenic variant c.1682A>G (p.Glu561Gly) within (LOD=4.09). Carriage of the missense variant resulted in increased relative abundance of Microbacteriaceae in the middle ear, along with occurrence of Microbacteriaceae in the outer ear and oral cavity but not the nasopharynx. Eight additional novel variants were identified in 12 families and individuals with OM. A role for in OM susceptibility is further supported by lower RNA counts in variant carriers, strong SPINK5 localisation in outer ear skin, faint localisation to middle ear mucosa and eardrum and increased expression in human cholesteatoma. CONCLUSION: variants confer susceptibility to non-syndromic OM. These variants potentially contribute to middle ear pathology through breakdown of mucosal and epithelial barriers, immunodeficiency such as poor vaccination response, alteration of head and neck microbiota and facilitation of entry of opportunistic pathogens into the middle ear.

Molecular outcomes, clinical consequences, and genetic diagnosis of Oculocutaneous Albinism in Pakistani population. - Shahzad, Mohsin; Yousaf, Sairah; Waryah, Yar M; Gul, Hadia; Kausar, Tasleem; Tariq, Nabeela; Mahmood, Umair; Ali, Muhammad; Khan, Muzammil A; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; et al. (Sci Rep, 2017)
Nonsyndromic oculocutaneous Albinism (nsOCA) is clinically characterized by the loss of pigmentation in the skin, hair, and iris. OCA is amongst the most common causes of vision impairment in children. To date, pathogenic variants in six genes have been identified in individuals with nsOCA. Here, we determined the identities, frequencies, and clinical consequences of OCA alleles in 94 previously unreported Pakistani families. Combination of Sanger and Exome sequencing revealed 38 alleles, including 22 novel variants, segregating with nsOCA phenotype in 80 families. Variants of TYR and OCA2 genes were the most common cause of nsOCA, occurring in 43 and 30 families, respectively. Twenty-two novel variants include nine missense, four splice site, two non-sense, one insertion and six gross deletions. In vitro studies revealed retention of OCA proteins harboring novel missense alleles in the endoplasmic reticulum (ER) of transfected cells. Exon-trapping assays with constructs containing splice site alleles revealed errors in splicing. As eight alleles account for approximately 56% (95% CI: 46.52-65.24%) of nsOCA cases, primarily enrolled from Punjab province of Pakistan, hierarchical strategies for variant detection would be feasible and cost-efficient genetic tests for OCA in families with similar origin. Thus, we developed Tetra-primer ARMS assays for rapid, reliable, reproducible and economical screening of most of these common alleles.
Keywords: Albinism, Oculocutaneous; Alleles; Female; Gene Frequency; Humans; Male; Membrane Transport Proteins; Mutation, Missense; Pakistan

Identification and clinical characterization of Hermansky-Pudlak syndrome alleles in the Pakistani population. - Yousaf, Sairah; Shahzad, Mohsin; Kausar, Tasleem; Sheikh, Shakeel A; Tariq, Nabeela; Shabbir, Asra S; Ali, Muhammad; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; Ahmed, Zubair M (Pigment Cell Melanoma Res, 2016)
Keywords: Adolescent; Adult; Alleles; Child; Child, Preschool; Female; Hermanski-Pudlak Syndrome; Humans; Infant; Male; Membrane Proteins; Middle Aged; Pakistan; Pedigree

Identification and functional characterization of natural human melanocortin 1 receptor mutant alleles in Pakistani population. - Shahzad, Mohsin; Sires Campos, Julia; Tariq, Nabeela; Herraiz Serrano, Cecilia; Yousaf, Rizwan; Jiménez-Cervantes, Celia; Yousaf, Sairah; Waryah, Yar M; Dad, Haseeb A; Blue, Elizabeth M; Sobreira, Nara; López-Giráldez, Francesc; et al. (Pigment Cell Melanoma Res, 2015)
Melanocortin 1 receptor (MC1R), a Gs protein-coupled receptor of the melanocyte's plasma membrane, is a major determinant of skin pigmentation and phototype. Upon activation by α-melanocyte stimulating hormone, MC1R triggers the cAMP cascade to stimulate eumelanogenesis. We used whole-exome sequencing to identify causative alleles in Pakistani families with skin and hair hypopigmentation. Six MC1R mutations segregated with the phenotype in seven families, including a p.Val174del in-frame deletion and a p.Tyr298* nonsense mutation, that were analyzed for function in heterologous HEK293 cells. p.Tyr298* MC1R showed no agonist-induced signaling to the cAMP or ERK pathways, nor detectable agonist binding. Conversely, signaling was comparable for p.Val174del and wild-type in HEK cells overexpressing the proteins, but binding analysis suggested impaired cell surface expression. Flow cytometry and confocal imaging studies revealed reduced plasma membrane expression of p.Val174del and p.Tyr298*. Therefore, p.Tyr298* was a total loss-of-function (LOF) allele, while p.Val174del displayed a partial LOF attribute.
Keywords: Alleles; Family; Female; Humans; Hypopigmentation; Male; Mutation; Pakistan; Pedigree; Phenotype; Receptor, Melanocortin, Type 1